ECONOMIC POTENTIAL BY MSMES AT COASTAL AREA: EVIDENCE OF BONE BALANGO REGENCY IN INDONESIA - Andi Yusniar Mendo; Idris Yanto Niode; Rahmawati Hasim; Vivin R. Daud (Dinasti Publisher, 2021)
The main aim of this research is to implement an application of the management models; micro, small, and medium-sized enterprises based on economic potential. The research applies a qualitative descriptive approach and the Analytic Hierarchy Process (AHP). This research has taken place at Bone Bolango Regency, Sulawesi, Indonesia. The result of the study shows that variable human resources and production operation are effective other three variables’ marketing, financial management, and institution are shows not that effective yet through the management model. This research finding shows that these fish farming enterprises have several challenges but through ability mind set increasing networking (AMIN) strategy, which is an effort in increasing the capacity and the ability of the businessmen in managing the productions, operational, administration management, financial and digital modernizations, and marketing network that will factually implicate in increasing the Micro, Small, and Medium-Sized Enterprises’ performance.